2020
DOI: 10.3390/nu12113483
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Status and Thyroid Function in a Group of Seaweed Consumers in Norway

Abstract: Seaweeds, or macroalgae, may be a good dietary iodine source but also a source of excessive iodine intake. The main aim in this study was to describe the iodine status and thyroid function in a group of macroalgae consumers. Two urine samples were collected from each participant (n = 44) to measure urinary iodine concentration (UIC) after habitual consumption of seaweed. Serum thyroid stimulating hormone (TSH), free thyroxine (fT4), free triiodothyronine (fT3), and peroxidase autoantibody (TPOAb), were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 48 publications
2
23
0
1
Order By: Relevance
“…While iodine deficiency causes hypothyroidism, iodine excess can cause both hyperthyroidism and hypothyroidism [ 141 ]. Studies in euthyroid humans have observed an increase in TSH levels after seaweed consumption [ 142 , 143 , 144 ] ( Table 1 ). However, Noahsen et al, observed a transient 150% increase in TSH levels in euthyroid individuals after consumption of seaweed (while fT4 levels remained unchanged) that returned to normal within three days [ 145 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While iodine deficiency causes hypothyroidism, iodine excess can cause both hyperthyroidism and hypothyroidism [ 141 ]. Studies in euthyroid humans have observed an increase in TSH levels after seaweed consumption [ 142 , 143 , 144 ] ( Table 1 ). However, Noahsen et al, observed a transient 150% increase in TSH levels in euthyroid individuals after consumption of seaweed (while fT4 levels remained unchanged) that returned to normal within three days [ 145 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…Although most healthy people tolerate high iodine intake well, in vulnerable individuals, it can lead to the development of hyperthyroidism and even hypothyroidism (reviewed in [ 233 ]). Causes of excess iodine are the consumption of overiodized salt, seaweeds (as already mentioned) [ 141 , 144 , 145 ], consumption of excess iodine through water and milk and taking diary supplements that contain iodine [ 234 ]. Most studies investigating the effect of high iodine intake on TSH and thyroid hormone levels in healthy adults observed an increase in TSH levels and a decrease in the levels of thyroid hormones after excess iodine [ 141 , 144 , 145 , 235 , 236 , 237 , 238 , 239 , 240 , 241 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…However, both deficiency and excess iodine can increase the risk of developing thyroid disorders. It is known that excessive iodine intake can result in both hypothyroidism and hyperthyroidism, with or without a goiter [27]. Therefore, it is important to monitor these different types of contaminants in seaweeds and seaweed extracts before consumption or use as ingredients in food, health, and cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with another study, where the estimated iodine content of commercial macroalgae products is estimated to be 6,000 μg/g, and the estimated iodine content per serving was exceeding 10,000 μg for several products ( 6 ). Excessive iodine status was observed in a study of Norwegian macroalgae consumers, where the median UIC was 1,200 μg/L, and the estimated iodine intake from macroalgae was 2,200 μg per day ( 36 ). A long-term excessive iodine intake has been associated with hypothyroidism, goitre, autoimmune thyroid disease and iodine-induced hyperthyroidism in epidemiological studies ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%